May Measurement Month 2017: an analysis of blood pressure screening results in China—East Asia. (24th April 2019) - Chen, Xin; Xu, Shao-Kun; Li, Yan; Sheng, Chang-Sheng; Guo, Qian-Hui; Yu, Wei; Li, Wei-Hua; Tang, Guo-Bao; Zhang, Hai-Feng; Dong, Yin; Wang, Sheng-Huang; Wang, Hong-Yu; et al.
Abstract: Elevated blood pressure (BP) is a growing burden worldwide, leading to over 10 million deaths each year. May Measurement Month (MMM) is a global initiative aimed at raising awareness of high BP and to act as a temporary solution to the lack of screening programmes worldwide. In China, several hypertension screening programmes are undertaken in the elderly in the community and in youths at university entrance and graduation. However, most people, especially the middle-aged working population, do not often have their BP measured. The current awareness (46.9%), treatment (40.7%), and control rates (15.3%) of hypertension remain low, while the proportion of screenees with hypertension is high in adult Chinese (23.2%). An opportunistic cross-sectional survey of volunteers aged ≥18 years was carried out in May 2017. Blood pressure measurement, the definition of hypertension and statistical analysis followed the standard MMM protocol. About 125 236 individuals were screened. After multiple imputation, with 124 623 as denominator, 32 089 (25.7%) had hypertension. Of the 103 981 individuals not on antihypertensive medication, 11 447 (11.0%) were hypertensive. Of the 20 547 individuals on antihypertensive medication, 7392 (36.0%) had uncontrolled BP (≥140/90 mmHg). An opportunistic screening may effectively identify those with high BP regardless of the use of antihypertensive medication and shows similar information on BP as a survey in a randomly selected population sample.